Fraud in the Sale and Purchase of Processed Wood in the Jambi Jurisdiction: Analysis of Positive Law and Islamic Criminal Law - Kemas Edy Haryanto; Rahmi Hidayati Al Idrusiah; Husin Bafadhal; Muhammad Farhan HR (Journal of Progressive Law and Legal Studies, 2026)
The practice of buying and selling processed wood in the Jambi jurisdiction plays a strategic role in supporting community economic activity. However, over time, this practice has been plagued by various legal irregularities, particularly fraud, resulting in economic losses, social conflict, and legal uncertainty. This study aims to analyze the obstacles and efforts to resolve fraudulent cases in the sale of processed wood, and to examine these acts from the perspective of Islamic criminal law. This study employed a qualitative approach with empirical juridical research. Data were obtained through interviews with law enforcement officials, processed wood business actors, and parties involved in the dispute. A literature review of laws and Islamic legal literature supported them. The results indicate that resolving fraud cases faces various obstacles, including blurred boundaries between civil breach of contract and criminal fraud, weak evidence of deception, a lack of written agreements, and low public legal literacy. Efforts to resolve these cases have been pursued through penal and non-penal channels, but neither is fully effective without proportional sanctions and ongoing prevention efforts. From an Islamic criminal law perspective, fraud in the sale and purchase of processed wood falls under the category of ta'zir crimes, which balance punishment, restitution for the victim's losses, and prevention of social harm. This research confirms that integrating Islamic criminal law values with positive law can strengthen substantive justice and property protection in community business practices.